Chord voicings and arpeggio patterns for vibraphone and marimba and other instruments - Richards, Emil. 1932-2019 (Malled Chord Studies, 2009)
Mallet Chord Studies provides exercises that cover the open and closed positions found in most jazz phrasings on keyboard instruments. The etudes are designed ti improve the improvisational skills needed to play all seventh chords in various open and closed positions.